Determining the Half Time and Analogy Constants of Radioactive Decay on the Illustration Board of Radioactive Decay with the Capacitor Filling and Discharging Method - Anggi Julvian Rachma; Delia Achadina Putri; Maria Ulfah; Dandan Luhur Saraswati (Universitas Muhammadiyah Makassar, 2019)
Radioactive decay is one of the material to be learned students in the study of physics. However, until now students only learn concepts through existing teaching materials. This is because, the level of danger is very high if students have to deal with radioactive elements. So, it does not allow students to experiment with decay directly. Through an illustration board of radioactive decay, students can learn radioactive decay events by illustrating radioactive decay by capacitor filling and emptying methods. In addition, through this props, students can determine the value of the decay constant and the half-life of a radioactive substance. Based on the results of experiments using capacitors (C) of 4700 μF and resistors (R) of 56 kΩ, the percentage of theoretical experimental data deviation is 2.63% for decay constants, and 3.06% for half-life. This illustrates that there is no significant difference from the theoretical experimental data. So, it can be concluded that the illustration board of radioactive decay is suitable to be used as an illustration tool for radioactive decay events and determine the value of the characteristics of radioactive decay (decay constant and half-life).Keywords: Props, Radioactive Decay, Half-Life, Decay ConstantPeluruhan radioaktif merupakan salah satu materi yang harus dipelajari siswa dalam bidang studi fisika. Namun, sampai saat ini siswa hanya mempelajari konsep melalui bahan ajar yang ada. Hal tersebut dikarenakan, tingkat bahaya yang sangat tinggi jika siswa harus berhadapan dengan unsur radioaktif. Sehingga, tidak memungkinkan siswa melakukan percobaan peluruhan secara langsung. Melalui alat illustration board of radioactive decay, maka siswa dapat mempelajari peristiwa peluruhan radioaktif melalui pengilustrasian peluruhan radioaktif dengan metode pengisian dan pengosongan kapasitor. Selain itu, melalui alat peraga ini siswa dapat menentukan nilai konstanta peluruhan dan waktu paruh dari suatu zat radioaktif. Berdasarkan hasil percobaan dengan menggunakan kapasitor (C) sebesar 4700 μF dan resistor (R) sebesar 56 kΩ, diperoleh persentase penyimpangan data percobaan dengan teoritis sebesar 2,63% untuk konstanta peluruhan, dan 3,06% untuk waktu paruh. Hal tersebut menggambarkan bahwa tidak terdapat perbedaan yang signifikan dari data hasil percobaan dengan teoritis. Sehingga, dapat disimpulkan bahwa alat illustration board of radioactive decay cocok untuk dijadikan alat ilustrasi peristiwa peluruhan radioaktif dan menentukan nilai karakteristik peluruhan radioaktif (konstanta peluruhan dan waktu paruh).Kata kunci: Alat Peraga, Peluruhan Radioaktif, Waktu Paruh, Konstanta Peluruhan